An introductory course in urology: results of a novel course for foundation doctors and medical students. (July 2014) - Abboudi, Hamid; Chetwood, Andrew; Nair, Rajesh; Bolgeri, Marco; Coker, Charles; Larner, Tim; Green, James
Objective: The objective of this article is to critically assess the value of a medical student and junior doctor weekend introduction to urology course. Materials and methods: All UK medical students and foundation doctors were invited to attend an introductory course held at The Royal Society of Medicine, London, organised by the Section of Urology. The course included consultant-delivered lectures, practical skills sessions and an academic competition. Pre- and post-course feedback questionnaires were used to assess (a) perceptions of urology as a specialty, (b) career aspirations and (c) confidence performing basic urological surgical skills. Results: Sixty delegates attended from a variety of UK medical schools and hospitals. Seventy-three per cent of respondents were more likely to pursue a career in urology post-course. The most common negative perceptions included being a competitive career with long training and lacking glamour. Confidence in suturing, knot tying, suprapubic catheterisation, basic laparoscopy and cystoscopy were significantly improved following this course ( p < 0.005). Conclusion: A short urology course should be offered to medical students by urology departments and surgical societies; it will benefit students as well as the specialty. It is important that medical students are exposed early to urology given both positive and negative perceptions. Such initiatives may help strengthen the positive perceptions and dispel negative perceptions while increasing delegates' desire to pursue a urology career.